KEBIJAKAN LUAR NEGERI INDONESIA SEBAGAI ANGGOTA TIDAK TETAP DEWAN KEAMANAN PBB PERIODE 2019-2020 - Yunita, Laila; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research will explain Indonesia's foreign policy during its time as a non-permanent member of the UN Security Council for the period 2019-2020. The struggle to become a non-permanent member of the UN Security Council is not a short process for Indonesia. The desire to become a non-permanent member of the UN Security Council has existed since 2009, but Indonesia officially announced its nomination in 2016. Until finally on June 8, 2018, Indonesia was successfully elected as a non-permanent member of the UN Security Council for the 2019-2020 period. This is the fourth time Indonesia has been entrusted with the task of being a non-permanent member of the UN Security Council, after being elected last in the 2007-2008 period. Therefore, this research will explain what foreign policies were made by Indonesia when it was elected as a non-permanent member of the UNSC for the 2019-2020 period, and what factors influenced Indonesia to take these policies.The research method used in this research is qualitative data analysis method with descriptive type. The data collection technique uses primary data collection methods and secondary data. Meanwhile, the level of analysis used in this research is the state level analysis. Based on the research results obtained, it can be seen that Indonesia's foreign policy when elected as a non-permanent member of the UNSC for the 2019-2020 period consists of 4 priorities and 1 main concern. These policies are creating a world peace ecosystem through a dialogue approach and active participation in UN peacekeeping missions, increasing synergy between the UN Security Council and regional organizations in overcoming conflicts in the region, increasing efforts to combat terrorism and extremism, ensuring synergy between peace building and sustainable development, as well as the Palestinian issue which is Indonesia's main concern in the UN Security Council. Meanwhile, there are also factors that influence Indonesia in making these policies, starting from setting internal and external motivation, information flow, the influence of various international politics, and the situation when decisions are made. Keywords : Indonesia, The UN Security Council, Foreign Policy